Role of polyamide microplastic in altering microbial consortium and carbon and nitrogen cycles in a simulated agricultural soil microcosm. (January 2023) - Sun, Xia; Tao, Ruidong; Xu, Daoqing; Qu, Mengjie; Zheng, Mingming; Zhang, Meng; Mei, Yunjun
Abstract: Microplastics (MPs) are persistent organic pollutants globally, with a continuous increase in MP wastes near and away from the regions of human activities. Studies to date aimed to explore the impact of MPs on ecosystems, but the area of research could not go beyond environmental pollution caused by MPs. To address the menace of MPs, scientists need to pay enough attention to the biogeochemical cycles, microbial communities, and functional microorganisms. Hence, this study aimed to evaluate the impact of adding 0.3% (mass ratio) [low-concentration (LC) group] and 1% [high-concentration (HC) group] of polyamide (PA) MP to the soil microenvironment with regard to the aforementioned parameters. PA MP decreased the soil microbial diversity (Shannon and Simpson indices, P < 0.05). At the phylum level, PA MP increased the abundance of Acidobacteria, Firmicutes, and Crenarchaeota (P < 0.05); at the genus level, it enhanced that of Geobacter, Thiobacillus, Pseudomonas, and Bradyrhizobium (P < 0.01) while decreased that of Bacillus, Flavisolibacter, Geothrix, and Pseudarthrobacter (P < 0.05). PA MP affected the carbon (C) cycle. PA MP accelerated the soil C fixation by enhancing the abundance of the genes accA and pccA . The LC PA MP accelerated organic C degradation and methane metabolism by changing the abundance of mnp, chiA, mcrA, pmoA, and mmoX genes, while the HC PA MP inhibited them with increasing the experimental time. Regarding the effects of PA on the nitrogen (N) cycle, the PA MP promoted N assimilation and ammonification by increasing the abundance of the genes gdh and ureC, the impact of PA MP on N fixation and denitrification depended on its concentration and treating time. This study showed that PA MP impacted the microbial consortium, it also affected the C and N cycles and its effect depended on its concentration and the treating time. Graphical abstract: Image 1 Highlights: PA MP significantly impacted the diversity of soil bacterial community. PA MP accelerated the soil carbon fixation. PA MP promoted the soil nitrogen assimilation and ammonification. The impact of PA MP on the C and N cycle depended on its concentration and treating time.